PENGARUH KELIMPAHAN KLEKAP DI TAMBAK TRADISIONAL TERHADAP PERTUMBUHAN IKAN BANDENG DAN UDANG WINDU - Sri Andayani (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2012)
This research aimed to know the density of klekap in traditional pond to increase the growth of milkfish and tiger shrimp. The method used descriptive approach. This research was conducted during 2 months, milkfish stocked size was 50 grams/fish of 1000 fish/ha and the shrimp were stocked is PL 20 (Post Larvae 20) by 4 rean/ha. Parameters measured the density of plankton and klekap, water quality and the growth of milkfish and tiger shrimp. The results showed that the klekap density (28.81–37.39 107 cell/m2), plankton (25.27 to 52.14 103 cell/l), and water quality was still supporting the growth of milkfish and tiger shrimp. The temperature from 26.5 to 35.5 0C; dissolved oxygen from 3.5 to 8.2 ppm, pH 6.9 to 8.0; salinity 28-35 ppt; ammonia 0.01-0.46 ppm; alkalinity 160.6 to 260.6 ppm; transparancy 33.0 to 53.5 cm; nitrate 0.1 to 0.47 ppm; orthophosphate 0.032 to 0.093 ppm. The results showed the growth of the average weight for milkfi sh 172.84 g/fish and shrimp reached 27.4 g/fish after 2 months maintained.